Biomarkers of Intestinal Injury in Colic - Elsa K. Ludwig; Kallie J. Hobbs; Caroline A. McKinney-Aguirre; Liara M. Gonzalez (Animals, 2023)
Biomarkers are typically proteins, enzymes, or other molecular changes that are elevated or decreased in body fluids during the course of inflammation or disease. Biomarkers pose an extremely attractive tool for establishing diagnoses and prognoses of equine gastrointestinal colic, one of the most prevalent causes of morbidity and mortality in horses. This topic has received increasing attention because early diagnosis of some forms of severe colic, such as intestinal ischemia, would create opportunities for rapid interventions that would likely improve case outcomes. This review explores biomarkers currently used in equine medicine for colic, including acute phase proteins, proinflammatory cytokines, markers of endotoxemia, and tissue injury metabolites. To date, no single biomarker has been identified that is perfectly sensitive and specific for intestinal ischemia; however, L-lactate has been proven to be a very functional and highly utilized diagnostic tool. However, further exploration of other biomarkers discussed in this review may provide the key to accelerated identification, intervention, and better outcomes for horses suffering from severe colic.